Pengaruh Model Pembelajaran Mind Mapping Dan Model Pembelajaran Inkuiri Terhadap Kemampuan Berpikir Kreatif Pada Peserta Didik Kelas IV Di Sekolah Dasar Kabupaten Demak - Candra Kristiyan; Sumarno Sumarno; Ida Dwijayanti (Institut Nalanda, 2023)
This study aims to analyze the influence of the mind mapping learning model and the inquiry learning model on the ability to think creatively in style material in elementary schools. Data collection techniques used were observation, questionnaires and written tests. Research instruments in the form of tests and questionnaires. The research sample was carried out by purposive sampling. Data analysis included test description analysis and questionnaire description analysis. Descriptive data on the post-test values of the control class with a sample of 20 students obtained a percentage value of 70.3%, while the experimental class with an inquiry model with a sample of 20 students obtained a percentage value of 85.3% and the experimental class with a mind mapping model with a total sample of 20 students obtained a percentage value of 84.8%. From the description of the post test value data, there are differences in the percentage values between the control class and the experimental class after being given different treatments. Descriptive data on the value of the questionnaire based on the results of data collection in the control class as a whole obtained a percentage value of 79.58%, based on the results of data collection in the inquiry experimental class as a whole obtained a percentage value of 81.58%, and based on the results of data collection in the mind mapping experimental class as a whole the overall percentage value obtained is 87.73%. The results for the post test scores in the control class with conventional learning and the inquiry experimental class are different. the percentage value in the control class is 70.3%. and inquiry experimental class of 85.3%. there was a difference of 15%. This shows that the ability to think creatively in style material is easier to obtain in the inquiry learning model than in conventional learning. The average learning outcomes in the post-test scores in the control class with conventional learning were 70.3% and the average post-test learning mind mapping was 84.8%. from these results there is a difference of 14.5%. This proves that mind mapping learning improves students' creative thinking abilities. So on the test instruments and questionnaires it can be concluded that there is an influence of the mind mapping learning model and the inquiry learning model on the ability to think creatively in fourth grade students in elementary schools.